Pengaruh Pendidikan Kesehatan Dengan Media Booklet Terhadap Kecemasan - dian, dian_therezah_yadi; Suzanna; Ayu Dekawaty (Citra Delima Scientific journal of Citra Internasional Institute, 2025)
Anxiety is a condition where someone feels uncomfortable accompanied by shadows of fear, alienation, accompanied by a sense of insecurity. Conditions of fear and uncertainty can convey a response to a situation where someone can predict a threatening situation so that someone can prepare themselves to face the situation. The purpose of this study was to determine the effect of health education using booklet media on client anxiety at the Muratara Palembang Shelter. The research design in this study was Pre-Experimental Pretest-Post Test Only One Group Design with a sample of 35 respondents. Results From the study it was found that health education using "booklet" media had an effect on anxiety in patients at the Muratara Palembang Shelter with a value of 0.00. With an average value of the client's anxiety level before being given health education with booklet media of 31.943. And the average value of the client's anxiety level after being given health education with booklet media was 23.029. It can be concluded that there is a decrease in the level of anxiety before being given health education using Booklet media with after being given health education using Booklet media taken from the p value of 0.000.